A two-section beam element to model the B-N covalent bonds in boron nitride nanotubes. (January 2022) - Zamani zakaria, Afshin
Highlights: A two-section beam element was formulated to characterize the covalent bonds of dissimilar atoms. Physical properties of the beam elements were obtained by minimization of the strain energy. Mechanical and vibrational properties of the boron nitride nanotubes (BNNTs) were considered as a benchmark. Young's modulus of the armchair BNNTs are higher than the zigzag counterparts, as shown by the developed model. Abstract: The ability of molecular mechanics to model the covalent bonds with equivalent elements is limited to the bonds connected with similar atom pairs. When dissimilar atoms are connected by covalent bonds, single-sectioned beam or spring elements could not capture the physical properties of the bond. In this respect, a molecular mechanics based two-sectioned beam element was formulated based on strain energy minimization and was used to model the elastic and vibrational characteristics of the boron nitride nanotubes (BNNT). Inconsistent conclusions given by the conventional molecular mechanics models were all rectified by the present formulation. It was shown that the armchair BNNTs has higher Young's modulus than that of zigzag counterparts. This was captured by the model with two-section beam elements, while single-section beam and equivalent spring elements are unable to predict this conclusion. The shear modulus of the zigzag BNNTs were 10 to 17 percent higher than the armchair counterparts. Graphical abstract: Image, graphical abstract